Los Angeles and the Summer Olympic Games Planning Legacies - Kassens Noor, Eva (SpringerBriefs in Geography,, 2020)
This open access book describes the three planning approaches and legacy impacts for the Olympic Games in one locale: the city of Los Angeles, USA. The author critically compares the similarities and differences of the LA Olympics by reviewing the 1932 and 1984 Olympics and by analyzing the concurrent planning process for the 2028 Olympics. The author unravels the conditions that make (or do not make) LA28's argument "we have staged the Games before, we can do it again" compelling. Setting the bid's promises into the contemporary local and global mega-event contexts, the author analyzes why LA won the bids, how those wins allowed LA to negotiate concessions with the IOC and NOC, and how legacies were planned, executed, and ultimately evolved. The author concludes with a prediction which 2028 legacy promises might and might not be fulfilled given the local and international Olympic contexts.